A Comparative Study of Deming's and Juran's Total Works: Changing the Quality Culture Towards Total Quality Management - Ahmed, Moyassar I. (جامعة كركوك - كلية الإدارة والاقتصاد, 2011)
يهدف البحث إلى إلقاء الضوء على الإسهامات الرئيسة لأثنين من رواد الجودة المشهورين الذين أسهموا في ثقافة الجودة لدى الشركات المختلفة على مستوى العالم. كما يبين التحول من الأفكار التقليدية لإدارة الجودة نحو فلسفة إدارة الجودة الشاملة من خلال محاورة اتجاهات مختلفة من التفكير لدى كل من Juran وDemingوصولا إلى تغطية الإسهامات التي ميزت كلاهما. تركزت المعضلة الفكرية في إمكانية تقديم معمارية تجمع بين فلسفتي، Juranو Demingمع تأشير الأهداف المتوخاة من هذه المعمارية وعوامل نجاح تطبيقها. توصل البحث إلى إمكانية استكشاف نقاط القوة في كلا الفلسفتين للحصول على التكامل والشمولية في مجال إدارة الجودة، على وفق ما تقدم ينقسم البحث إلى مقدمة وستة أجزاء هي: 1- المنهجية. 2- الأعمال الكاملة لـ. Deming 3- الأعمال الكاملة لـ Juran. 4- مطابقة الفلسفتين. 5- المعمارية المقترحة. 6- الخلاصة.
The current paper aims to shed light on the major contributions of the famous two pioneers in quality culture at all companies of the world. It also shows the convert of classical ideas in quality management towards the philosophy of TQM .Different sides of thinking have been indicated. The study also covered the major contributions of both authors. The dilemma was shown in the possibility of introducing a paradigm ingather the Deming's and Juran's philosophies. The paper decided a major target in contact with the proposed paradigm and the factors of success. The paper concluded into the possibility of exploring the strength points of both philosophies to gain the totality of quality management. Thus, the paper is contain of introduction and six sections, they are: 1- Methodology 2- Deming's Total Works 3- Juran's Total Works. 4- Matching the Two philosophies 5- Suggested paradigm. 6- Conclusions
Keywords: الشركات -- إدارة الجودة -- رواد الجودة -- ديمنغ، ويليام ادواردز -- جوران، جوزيف موسى